１種以上の極性油、Ｃ２～Ｃ６脂肪族モノアルコール及びポリオール、少なくとも１種の親水性活性薬剤を含み、７質量％未満の水を含む化粧用組成物 (2022)
【課題】本発明は、ケラチン物質の美容的処理のための組成物及びその美容的使用を提供する。【解決手段】本発明の主題は、－組成物の総質量に対して３０質量％～８９質量％の少なくとも１種の極性油；－組成物の総質量に対して１０質量％～４５質量％の少なくとも１種のＣ２～Ｃ６脂肪族モノアルコール；－組成物の総質量に対して０．５質量％～５０質量％の少なくとも１種のポリオール；－少なくとも１種の親水性活性薬剤を含み、組成物の総質量に対して７質量％未満の水を含む化粧用組成物である。本発明は、関連する美容的方法及び前記組成物の美容的使用にも関する。【選択図】なし A subject of the invention is a cosmetic composition comprising: -from 30% to 89% by weight of at least one polar oil relative to the total weight of the composition; -from 10% to 45% by weight of at least one C2-C6 aliphatic monoalcohol relative to the total weight of the composition; -from 0.5% to 50% by weight of at least one polyol relative to the total weight of the composition; -at least one hydrophilic active agent, said composition comprising less than 7% by weight of water relative to the total weight of the composition. It also relates to the associated cosmetic process and also the cosmetic use of said composition.